Abordagens para o problema integrado de dimensionamento e sequenciamento de lotes da produção de bebidas - Ferreira, Deisemara (2006)
The object of this study is the integrated problem of lot sizing and scheduling of the soft drink production. Such problem consists of deciding how much to produce of each drink and in each period and in which sequence, in order to satisfy the demand and to minimize the costs of storage, backlogging and changeover. The set up times of the machines are sequencedependent, consequently the production scheduling is complex. The problem is capacitated, multi-item, with changeover times and costs dependent of the sequence. In this study we propose three mixed integer optimization models and solution approaches to solve the problem. The models are based in cases studies of a large soft drink facility, and a small facility. We developed relax and fix heuristics to solve de models. The results show that the proposed strategies are competitive when we compare with solutions of the facilities.